Pelayanan Gratis Pemeriksaan Kadar Hemoglobin Ibu Hamil Di Kelurahan Mosso Kabupaten Majene - Diana, Sitti Aras; Anita, Nur (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Checking Hb levels is an effort to early detect anemia in pregnant women. Anemia most often occurs in pregnant women, where pregnant women are diagnosed with anemia if the Hb level is below 11gr/dl. One effort that can be made to deal with the problem of anemia in pregnancy is through health education, because providing knowledge such as health education or counseling can aim to increase pregnant women's knowledge about handling anemia in pregnancy. Objective: The aim of this activity is to increase public knowledge about educating pregnant women in preventing iron deficiency anemia and HB examination. Method: The method used in this activity is conducting a preliminary study for community service implementation activities, then making preparations for implementing community service, including the location of the activity implementation, determining targets, and the time for implementing the activity. Result: The results of the service carried out were that of the 24 pregnant women who were examined, there were 7 (29%) pregnant women who had mild anemia, and 1 (4%) pregnant woman who had moderate anemia. Conclusion: The conclusion obtained from community service activities in Mosso Village, Sendana District, Majene Regency, is that it can provide information to pregnant women regarding their health picture, whether they have anemia or not, as well as providing them with knowledge regarding how to prevent pregnant women who experience health problems from experiencing problems or complications. What can happen can be prevented.